Quantitative analysis of transmutation nuclides in pure tungsten irradiated with high-energy protons and spallation neutrons at 6.4 and 28 dpa - Vicente Araullo-Peters; Yong Dai (Nuclear Materials and Energy)
Tungsten is a key material for applications of spallation targets and fusion reactors. Irradiation-induced transmutation products can significantly affect the mechanical and thermal properties of tungsten. However, detailed quantitative analysis of transmutation elements of irradiated tungsten has not been reported and is therefore in high demand, especially in the cases of spallation targets where a large amounts of transmutation elements are produced. In this work, we analyzed the transmutation products in pure tungsten samples irradiated in a target of Swiss Spallation Neutron Source (SINQ) at doses of 6.4 and 28 dpa, the latter being the highest dose ever achieved in spallation targets. Quantitative measurements of 40 nuclides ranging from 144Sm to 188Os were performed using the atom probe tomography (APT) technique. The measured concentrations of transmutation elements are in good agreement with those of neutronic calculations. The APT analysis also revealed clusters of transmutation elements. Due to low irradiation temperature (<500 °C) and low concentration of transmutation elements, the clusters are 1–2 nm in diameter.